Strategi Coping Terhadap Stress Kerja Pada Perawat di Rumah Sakit: Literatur Review - Rina Hardiyanti; Iman Permana (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Increased work stress on nurses is caused by the high demands of work and must be maximal in serving patients at the hospital. Nurses are required to have a way of completing and adjusting conditions to the problem which is usually referred to as coping, so that they can carry out their professional work professionally. Objective: To find out the coping strategies used by nurses in dealing with work stress in the hospital environment. Method: This literature review uses database the Ebsco, Google Scholar, DOAJ, and Pubmed. At the beginning of the search with keywords: "Coping Strategy" OR "Work Stress" AND "Nurse" obtained a total of 536,394 articles, after being screened by observe the inclusion criteria obtained 10 international articles from 2015 to 2019. Results: Stress relationships and coping strategies, indicate that the level of work pressure will be low when nurses take a positive coping strategy in the face of work stress. Some of the factors that influence coping from the literature results include self-concept, socio-economic status, social support, experience, social skills, and personality characteristics. Conclusion: Nurses in handling work stress prefer to use adaptive coping strategies that focus on problem focused coping rather than using emotion focused coping.